Women in Sexual Harassment News in Indonesian Online Media - Latif Fianto; Fendiyatmi Kusufa; M. Abdul Ghofur; Mohammad Askiyanto (Jurnal Komunikasi Nusantara, 2024)
Sexual violence experienced by women is nothing new. However, reports in various mass media have left women in an increasingly worse position. This research is intended to uncover and analyze in depth the position of women in online media news texts. This research was operated using quality research, which specifically uses the discourse analysis method which was coined or developed by Sara Mills. The research results explain that the subject position explains the event or thing that is the object. Different from the subject-object position, the writer-reader position explains the writer's position when writing news text and the reader's position when reading the news text that has been written. The reader's position describes what kind of position the author wants to control the reader when reading the text. From this analysis it emerged that the position of women in the subject-object relationship in news texts is still placed as an object, where the existence of women is still ignored. Their existence in the text is represented by other parties who are men, so that women cannot represent themselves, either in social reality or in the text. Abstrak Kekerasan seksual yang dialami perempuan sudah bukan hal baru. Akan tetapi pemberitaan di berbagai media massa telah menyebabkan perempuan berada di posisi yang semakin buruk. Penelitian ini dimaksudkan untuk membongkar sekaligus mengalisa secara mendalam posisi perempuan dalamm teks berita media online. Penelitian ini dioperasikan dengan menggunakan penelitian kaulitas, yangs ecara khusus menggunakan metode analisis wacana yang dicetuskan atau dikembangkan oleh Sara Mills. Hasil penelitian menjelaskan bahwa posisi subjek menjelaskan peristiwa atau sesuatu hal yang menjadi objek. Berbeda dengan posisi subjek-objek, posisi penulis-pembaca menjelaskan bagaimana posisi penulis ketika menulis teks berita dan bagaimana posisi pembaca ketika membaca teks berita yang sudah ditulis tersebut. Posisi pembaca menggambarkan posisi seperti apa yang ingin dikendalikan oleh penulis terhadap pembaca ketika membaca teks. Dari analisis ini kemudian dihasilkan bahwa posisi Perempuan dalam relasi subjek-objek dalam teks berita masih ditempatkan sebagai objek, di mana keberadaan Perempuan masih terabaikan. Keberadaannya di dalam teks diwakili oleh pihak lain yang notabene laki-laki, sehingga Perempuan tidak bisa merepresentasikan diri mereka sendiri, baik di realitas sosial maupun di dalam teks.